EFFECT OF RICE STRAW ON SOME BLOOD BIOCHEMICAL PARAMETERS OF IRAQI BUFFALO (Bubalus Bubalis) - Ali J. I.; W. H. Al-Samaraae (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to show the changes of some blood parameters by the effect of biological and chemical treatment of rice straw ,It was conducted at The Ruminant Research Station in Abu Ghraib / Directorate of / Agricultural Researches / Ministry of Agriculture, for the period from June 1, 2021 until August 27, 2021 (preceded by the preliminary period 14 days), The study included 12 Iraqi buffalo calves aged 5 - 6 months. the calves were randomly divided into three equal groups (4 calves / group), kept in individual pens and distributed among group.T1 (the control group) in which the calves were fed on untreated rice straw T2 the calves were fed on rice straw treated with urea at a rate of 3% T3 the calves were fed on rice straw treated with Trichoderma harzianum at a rate of 0.1%. The triglycerides concentration were decreased significantly (p≤0.05) in the T2 (11.28 mg/dL) and T3 (11.32 mg/dL) compared with T1 (20.79 mg/dL). similarly, the level of very low-density lipoprotein (vLDL) was decreased 2.25, 2.26, 4.16 mg/dL for T2, T3, and T1, respectively. The creatinine concentration in T2(87.19 mmol/L) was significantly decrease than that of T1(177.8 mmol/L) and T3(176.75 mmol/L). Also, ALP concentration increased in T2 (238.93 IU/liter) compared with T1. (151.82 IU/liter), while it did not differ significantly with T3( 205.83 IU/liter) Also T3 did not differ significantly from T1. The differences in the concentration of lipid profile, protein fractions and enzymes activity among groups lacked significance , feeding of rice straw treated biologically and chemically had no negative effect on buffalo calves health.